Social protection coverage - Sudan case study - Fabianna Bacil; Wesley de Jesus Silva (International Policy Centre for Inclusive Growth (IPC-IG), 2020)
This case study aims to measure the coverage of social protection in Sudan, by analysing the extent to which the diverse risks faced by the different groups are covered. Data from the National Household Budget and Poverty Survey (NHBS) 2014-2015 shows that the governmental provision of social protection in Sudan has the smallest contribution to mitigate risks with an average protection coverage rate of only 0.4% vs. an average of 1.3% for informal social protection.
Keywords: 330; social protection; coverage; life cycle risks; SDG 1.3; household survey; Sudan